Beyond good : how to be a great PhD supervisor the art of inspiring and guiding doctoral students - Amitabh Anand; Fernandes, Edmond (Mangalore Global South Strategies, 2025)
Understanding the Supervisors Responsibilities; Effective mentorship Techniques; Balancing guidance and Promoting Independent Thinking; Conflict Resolution in Supervision; Time management Prioritizing tasks and Responsibilities; Cultivating a Supportive Research Culture; Providing Constructive Feedback; Supporting Mental Health and Wett-being; the future of Ph D Supervision Adapting to changes; Supervisors role in Research ethics and conduct; Preparing Doctoral students for thesis defense; informative research tools for supervisors; Commandments for Supervisors
Keywords: Higher Education